2015
DOI: 10.3855/jidc.6195
|View full text |Cite
|
Sign up to set email alerts
|

Colistin alone or combined with sulbactam or carbapenem against A. baumannii in ventilator-associated pneumonia

Abstract: Introduction: Colistin use has increased over the last ten years because of multidrug-resistant microorganisms. The aim of this study was to compare the clinical and microbiological efficacy of colistin alone or in combination with sulbactam or carbapenem in the treatment of ventilator-associated pneumonia (VAP) due to multidrug-resistant (MDR) and extremely drug-resistant (XDR) A. baumannii. Methodology: Cases treated for VAP because of MDR and XDR A. baumannii between January 2011 and January 2013 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 36 publications
6
50
0
1
Order By: Relevance
“…A similar conclusion was draw in XDR A. baumannii pneumonia (VAP and hospital-acquired pneumonia) by Khawcharoenporn T et al (56). But as mentioned before, Yilmaz GR et al also (31) reported that clinical and microbiological response was better in a colistincarbapenem group than a colistin-sulbactam group in VAP due to MDR or XDR A. baumannii. Mortality rates were also found to be lower in a colistin-carbapenem group, although with no statistical difference.…”
Section: Colistin-carberpenem Vs Colistin-sulbactamsupporting
confidence: 70%
See 3 more Smart Citations
“…A similar conclusion was draw in XDR A. baumannii pneumonia (VAP and hospital-acquired pneumonia) by Khawcharoenporn T et al (56). But as mentioned before, Yilmaz GR et al also (31) reported that clinical and microbiological response was better in a colistincarbapenem group than a colistin-sulbactam group in VAP due to MDR or XDR A. baumannii. Mortality rates were also found to be lower in a colistin-carbapenem group, although with no statistical difference.…”
Section: Colistin-carberpenem Vs Colistin-sulbactamsupporting
confidence: 70%
“…intravenous polymyxins alone in MDR GNB infections, most of which were pneumonias. It's indicated that the mortality ranged from 0% to 74.3% (4,21,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), clinical response (cure and improvement) rate 7-82.1%, and microbiological eradication 27.3-73.9% (24,(33)(34)(35)(36)(37)(38). In respect to the colistin only susceptible strains, it's reported that the mortality in hospitals of intravenous colistin monotherapy was 50% (16/32) (Figure 2), 11 patients died in Intensive Care Unit (ICU) (39), and clinical cure was obtained in 82.1% of infectious episodes (23/28) and bacteriological clearance was achieved in 73.9% (17/23) of the cured infectious episodes (38).…”
Section: Combination Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Zakażenia spowodowane przez A. baumannii wywołane są głównie przez szczepy wielolekooporne, co stwarza problem terapeutyczny, dlatego rezultat rekombinowanej terapii ocenia się jako wybór pozwalający na skuteczną eradykację drobnoustrojów [14,15]. W związku z tym do leczenia celowanego w OIT często stosowano antybiotykoterapię skojarzoną m.in.…”
Section: Dyskusjaunclassified